Psychometric Validation of a Marriage Readiness Instrument for University Students Using Rasch Analysis - Aprilia Setyowati; Fatia Dwi Nur Aini; Amien Wahyudi; Mufied Fauziah; Fadhila Malasari Ardini; Mualwi Widiatmoko (Indonesian Journal of Educational Counseling, 2026)
Marriage readiness is an important developmental aspect among university students, encompassing emotional and social maturity as well as the ability to perform marital roles. However, psychometrically sound instruments for measuring marriage readiness remain limited, particularly within the Indonesian guidance and counseling context. This study aimed to validate the Marriage Readiness instrument for university students using the Rasch Measurement Model to determine its feasibility as a psychological assessment tool. A quantitative approach was employed involving 217 students and 40 instrument items analyzed using Winsteps version 4.4.5. The analysis included person and item reliability, item fit, unidimensionality, and mapping of respondents’ abilities and item difficulty through the Wright map. The results indicated good psychometric quality, with person reliability of 0.92 and item reliability of 0.95. Most items met the Rasch model criteria, although several misfitting items were identified and required revision. Unidimensionality analysis showed that the instrument consistently measured a single underlying construct, with a raw variance explained by measures of 40.9%. The Wright map demonstrated an appropriate alignment between item difficulty and respondent characteristics. Therefore, the Marriage Readiness instrument is feasible for use as an assessment tool in guidance and counseling services to identify university students’ level of marriage readiness.